Assessing the determinant factors of risk strategy adoption to mitigate various risks: An experience from smallholder rubber farmers in West Kalimantan Province, Indonesia - Imelda Imelda; Mulyo Jangkung Handoyo; Suryantini Any; Masyhuri Masyhuri (Open Agriculture, 2023)
Over the past decade, smallholder rubber farming experienced significant issues related to risks of rainy season, rubber diseases, and price decreases. The risk exposure will reduce agricultural productivity, income, and sustainability. Farmers are expected to mitigate various risks by adopting the appropriate risk strategy. Efforts to support the risk strategy adoption are constrained by the lack of scientific research in rubber farming, especially for simultaneous risk strategy adoption. This study aims to identify the risk strategy adoption in rubber farming and analyse the determinant factors by considering farmers’ socioeconomic, rubber farm characteristics, and risk perception. The data were collected from 200 rubber farmers in West Kalimantan, Indonesia, and analysed using a multinomial logit model. The study results show that the most selected strategy was income diversification. The multinomial logit model indicates that farmers’ age, family members, rubber age, rubber clones, and rainy season risk perception positively affect the adoption of risk strategy. In contrast, experience, farm area, and farm distance have a negative effect. The results also indicate that family members, farm area, and farm distance variables significantly affect all choices of risk strategy adoption. The results of this study suggest several implications for government and policymakers in providing assistance and counselling, capital assistance, input access, and improving transportation, road access, and communication.